Development of an Excel Dashboard-Based Warehousing Administration System Using the Design Thinking, EOQ, and POQ Approaches - Samuel Christian Hamonangan Silitonga Nim; Firman Hawari (Jurnal Indonesia Sosial Teknologi, 2024)
Warehousing is an important part of a manufacturing process where ideal warehouse management will improve the company's logistics in times of crisis. This research seeks to gain an in-depth understanding of the problems faced by warehousing and create user-focused solutions. Furthermore, EOQ and POQ methods are used to optimize stock and order management. EOQ helps determine the economical number of bookings to be made, while POQ considers demand variability in determining order schedules. The results of this study show that with Design Thinking, it was found that the needs of users are the use of an easier application system and stock filling standards so that the accuracy of stock is better maintained. It can be concluded that the EOQ and POQ methods can overcome understock and overstock. However, the EOQ method has less risk than POQ, this is because the company does not spend a lot of funds and takes with little frequency so it is more effective and the warehouse movement space can be more minimal.